2012
DOI: 10.1101/cshperspect.a013482
|View full text |Cite
|
Sign up to set email alerts
|

 -Thalassemia Intermedia: A Clinical Perspective

Abstract: Our understanding of the molecular and pathophysiological mechanisms underlying the disease process in patients with b-thalassemia intermedia has substantially increased over the past decade. Earlier studies observed that patients with b-thalassemia intermedia experience a clinical-complications profile that is different from that in patients with b-thalassemia major. In this article, a variety of clinical morbidities are explored, and their associations with the underlying disease pathophysiology and risk fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
89
1
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(102 citation statements)
references
References 120 publications
(164 reference statements)
7
89
1
5
Order By: Relevance
“…This is quite different from a study by Camaschella et al 8 , which found that 42% of intermediate thalassemia patients in Italy did not require transfusion. This discrepancy may be due to a difference in the type of mutation, clinical scoring criteria, and management of the patients.…”
contrasting
confidence: 56%
See 1 more Smart Citation
“…This is quite different from a study by Camaschella et al 8 , which found that 42% of intermediate thalassemia patients in Italy did not require transfusion. This discrepancy may be due to a difference in the type of mutation, clinical scoring criteria, and management of the patients.…”
contrasting
confidence: 56%
“…It was in accordance to other studies, which also found that the age at diagnosis for this group ranged from 2 to 8 years. 7,8 From physical examination, the subjects in this study who were diagnosed after the age of 10 had already manifested severe complications, including changes in facial bone structure, delayed puberty, growth disorders, and splenomegaly. Similarly, a study from Thailand found that the subjects from the severe group who did not receive adequate transfusion may acquire complications in the first decade of life.…”
mentioning
confidence: 99%
“…b-Thal intermedia clinically differs from major and minor ones with respect to necessity of transfusion. The degree of anemia for b-Thal major is more aggravated than the grade of anemia for bThal intermedia [5,8]. The genotype of b-Thal intermedia is mostly homozygotes or compound heterozygotes [6].…”
Section: Introductionmentioning
confidence: 94%
“…Para spinal location of EMH has been noted in 11-15% cases. [4][5][6][7] However Koch et al reported para spinal location in only 0.6% cases of EMH. [8] Even amongst these, around 80% remain asymptomatic, detected incidentally on radiological imaging.…”
Section: Case Reportmentioning
confidence: 99%